Políticas Públicas De Formação Inicial De Professores De Educação Básica: Um Estudo Sobre O Pibid - Ros, Cristina Vitorino Da [UNIFESP] (2017)
Abstract: This thesis analyzes the historical, political and pedagogical bases of the Institutional Program of Initiatives for Teaching (Pibid), and also seeks to understand how the process of implementation of the program occurs, considering the reports of the subjects that Participate - specifically the students and teachers of the school. The Pibid was implemented in 2007, in the context of correlations of social and political forces, both internal, in which the enlarged state manages Brazil's fragile social, educational and political situation in favor of the economic as well as the external bases, as regards the orientation of multilateral bodies in the international context. One of the main objectives of Pibid is to establish a system of collaboration between university and public school to train new teachers, creating as locus of production of knowledge and teaching knowledge both educational spaces involved. Faced with the precarious conditions of teaching work, in which technological rationality predominates, the program commits itself to narrow the relations between theory and practice through the formative experience of the graduates in formation with the training teachers both those who work in the university and those who work in public school. The thesis that is intended to defend is to denaturalize the Salvationist character attributed to the Pibid and attentive to the regulatory role of public educational policies. To do so, the paths of qualitative research were traced through a case study. In the data collection, the observer's field diary was used, along with semi-structured interviews to listen and analyze the subjects that compose the program, since it is considered of paramount importance to analyze and apprehend the considerations coming from the undergraduate students and the regent teachers in the school Public. The research was carried out with fifteen subjects, in a determined subproject of the Pedagogy course, involving a public university and a public school of basic education, both located in the periphery of the metropolitan region of São Paulo. The approach with the subjects of the research made it possible to access the context of the educational policy execution, to apprehend the subjectivity of the subjects and to cross the data with the observations of the field diary, in a spiral movement of reflection and critical analysis, from the moment of the collection of data, going through deepening of the theory, which culminated in the analysis of the subjects' point of view. It is concluded that the hypothesis is confirmed, since although the Pibid points, through small fissures, some emancipatory possibility supported by collective work, the character of conformation reigns through the current state of flexibility of working conditions on the school floor. The concrete conjuncture to which public school workers are exposed successively conditions the look and action of the undergraduate students, in accordance with the current state of precarious working conditions and training in the face of the rationality of time and space, naturalizing the veiled proposition of the minimum learning for the students of the public school of basic education.